STABILITY OF OPEN MINE SLOPE USING THE LIMIT EQUILIBRIUM METHOD AND RISK ANALYSIS TO SUPPORT MINING INFRASTRUCTURE PLANNING - Irianto; Afasedanya, Mapuay Menasye Theo (INTAN Jurnal Penelitian Tambang, 2025)
Slope stability is a critical aspect in open-pit mining operations, particularly in limestone (C Group Mining) quarries that are widely developed in the Polimak area, Jayapura City. This study aims to evaluate slope stability under various slope geometries and hydrogeological conditions, as well as to establish a relevant risk map to support the design of safe and sustainable slopes. The methodology involved field surveys to collect slope geometry data and soil-rock samples, followed by laboratory testing to determine key geotechnical parameters (cohesion, internal friction angle, unit weight, and UCS). Slope stability analysis was performed using the Limit Equilibrium approach with Slide2 software, considering different combinations of slope heights (10–20 m), angles (45°–65°), and drainage conditions (dry vs. saturated). The results indicate that increasing slope height and angle significantly reduces the Factor of Safety (FoS), while rising groundwater levels due to rainfall can further decrease FoS by up to 20%. For instance, a 20 m high slope at 65° under saturated conditions yielded an FoS of only 0.73, far below the minimum safety threshold (FoS ≥1.3). Based on the risk matrix, such conditions fall into the high to extreme risk categories. This study recommends implementing multi-bench slopes with a maximum angle of 45°, complemented by proper drainage systems to maintain stability. The findings are expected to serve as practical guidance for managing limestone quarry operations in Polimak to ensure safe and efficient mining activities.